Teacher Identity in the South Korean Academy System - Story, Adam (2016)
This study reports on a qualitative investigation of the professional identity construction of 15 unqualified native English teachers currently working in the South Korean academy system – an area neglected by much past research. By viewing teacher identity as a discursive construction, influenced by social and institutional pressures, the study draws on the insights offered by poststructuralist theory, Wenger’s (2010) communities of practice concept, and the findings of past empirical research, to analyse how the participants view themselves as teachers. The findings, based on questionnaire and semi-structured interview responses, suggest that whilst the teachers may lack professional teaching qualifications, and may not be committed to English language teaching as a long term career, they still possess a desire to engage in critical reflective practice and a will to exert their own agency. However, their identities as teachers are at times curtailed by the marginalisation they experience in their institutions and by their lack of a long term career focus. This study therefore calls for closer collaboration between native teachers and their Korean superiors, and for more support and in-service training for native teachers currently employed in Korea. The findings of this study have implications for stakeholders in the Korean academy system, as well as the wider TESOL profession.